A randomised double-blind control study of early intracoronary autologous bone marrow cell infusion in acute myocardial infarction (REGENERATE-AMI). Issue 2 (18th February 2014) - Hamshere, Stephen; Choudhury, Tawfiq; Jones, Daniel A; Locca, Didier; Mills, Peter; Rothman, Martin; Knight, Charles; Parmar, Mahesh; Agrawal, Samir; Martin, John; Mathur, Anthony
Abstract : Introduction: Acute myocardial infarction (AMI) remains a major cause of mortality and morbidity worldwide despite the latest therapeutic advances designed to decrease myocardial injury. Preclinical and emerging clinical evidence show that the intracoronary injection of autologous bone marrow mononuclear cells (BMCs) following AMI leads to improvement in left ventricular ejection function (LVEF). In this clinical trial we will for the first time assess the effect of early (<24 h) infusion of autologous BMCs following AMI on cardiac function. Methods and analysis: REGENERATE-AMI is a double-blind, randomised, multicentre, placebo-controlled trial to determine whether early (<24 h) intracoronary infusion of BMCs improves LVEF after AMI. The study will enrol 100 patients presenting with an anterior AMI demonstrating anterior regional wall motion abnormality. Patients will be randomised to receive intracoronary infusion of BMCs or placebo (0.9% saline). Primary endpoint will be change in LVEF at 1 year compared to baseline, measured by cardiac MRI. Secondary endpoints at 6 months include the change in global LVEF relative to baseline measured by quantitative left ventriculography and echocardiography, as well as major adverse cardiac events which is also measured at 1 year. Ethics and dissemination: The study will be performed in agreement with the Declaration of Helsinki and is approved by local ethics committee (NRES Committee London West London: 07/Q0603/76). Trial registration: http://clincialtrials.gov (NCT00765453 ). The results of the trial will be published according to the CONSORT statement and will be presented at conferences and reported in peer-reviewed journals.